证明1/1-tanα-1/1+tanα=tan2α

来源:学生作业帮助网 编辑:作业帮 时间:2017/06/28 22:12:10
证明:tanαtan2α+tan2αtan3α+……+tan(n-1)αtan(nα)=tan(nα)/tanα-n

证明:tanαtan2α+tan2αtan3α+……+tan(n-1)αtan(nα)=tan(nα)/tanα-n证明:tanαtan2α+tan2αtan3α+……+tan(n-1)αtan(nα

证明:tanθ-(1/tanθ)=-2/tan2θ

证明:tanθ-(1/tanθ)=-2/tan2θ证明:tanθ-(1/tanθ)=-2/tan2θ证明:tanθ-(1/tanθ)=-2/tan2θ

证明tanα-1/tanα等于2/tan2α 现等

证明tanα-1/tanα等于2/tan2α现等证明tanα-1/tanα等于2/tan2α现等证明tanα-1/tanα等于2/tan2α现等tanα-1/tanα=sinα/cosα-cosα/s

若1 tanα/1-tanα=2008,则tan2α1+ tanα/1-tanα=2008,则tan2α

若1tanα/1-tanα=2008,则tan2α1+tanα/1-tanα=2008,则tan2α若1tanα/1-tanα=2008,则tan2α1+tanα/1-tanα=2008,则tan2α

tan2α=1/3,tanα等于多少

tan2α=1/3,tanα等于多少tan2α=1/3,tanα等于多少tan2α=1/3,tanα等于多少3±根号10

已知tan2α =1/3则tanα

已知tan2α=1/3则tanα已知tan2α=1/3则tanα已知tan2α=1/3则tanα根据二倍角公式 tan2α=2tanα/[1-(tanα)]=1/3得到tana=1/71/(3+√10

已知tan2α=1/3 求tanα

已知tan2α=1/3求tanα已知tan2α=1/3求tanα已知tan2α=1/3求tanαtan2α=1/32tana/(1-tana^2)=1/36tana=1-tana^2tana^2+6t

tan(2α-β)是怎么化成(tan2α-tanβ)/[1+tan2αtanβ) 用了什么公式?

tan(2α-β)是怎么化成(tan2α-tanβ)/[1+tan2αtanβ)用了什么公式?tan(2α-β)是怎么化成(tan2α-tanβ)/[1+tan2αtanβ)用了什么公式?tan(2α

已知tan(α+β)=-1,tan(α-β)=1/2,则tan2α/tan2β的值为

已知tan(α+β)=-1,tan(α-β)=1/2,则tan2α/tan2β的值为已知tan(α+β)=-1,tan(α-β)=1/2,则tan2α/tan2β的值为已知tan(α+β)=-1,ta

已知tan(α+β)=1,tan(α-β)=1/2,求tan2α,tan2β的值

已知tan(α+β)=1,tan(α-β)=1/2,求tan2α,tan2β的值已知tan(α+β)=1,tan(α-β)=1/2,求tan2α,tan2β的值已知tan(α+β)=1,tan(α-β

已知(1+tan2α)/(1-tanα)=2010,求(1/cos2α)+tan2α

已知(1+tan2α)/(1-tanα)=2010,求(1/cos2α)+tan2α已知(1+tan2α)/(1-tanα)=2010,求(1/cos2α)+tan2α已知(1+tan2α)/(1-t

求证cos4α*tan2α-sin4α=2tanα/tan方α-1

求证cos4α*tan2α-sin4α=2tanα/tan方α-1求证cos4α*tan2α-sin4α=2tanα/tan方α-1求证cos4α*tan2α-sin4α=2tanα/tan方α-1证

(1+tanα)/(1-tanα)=2008,则(1/cosα)+tan2α=?

(1+tanα)/(1-tanα)=2008,则(1/cosα)+tan2α=?(1+tanα)/(1-tanα)=2008,则(1/cosα)+tan2α=?(1+tanα)/(1-tanα)=20

若(1+tanα)/(1-tanα)=2008 则1/cos2α+tan2α=

若(1+tanα)/(1-tanα)=2008则1/cos2α+tan2α=若(1+tanα)/(1-tanα)=2008则1/cos2α+tan2α=若(1+tanα)/(1-tanα)=2008则

1+tanα/1-tanα=2006则1/cosα+tan2α=?

1+tanα/1-tanα=2006则1/cosα+tan2α=?1+tanα/1-tanα=2006则1/cosα+tan2α=?1+tanα/1-tanα=2006则1/cosα+tan2α=?(

(tanα+1)/(1-tanα)=2010 求sec2α+tan2α

(tanα+1)/(1-tanα)=2010求sec2α+tan2α(tanα+1)/(1-tanα)=2010求sec2α+tan2α(tanα+1)/(1-tanα)=2010求sec2α+tan

求证tan2分之α-1/tan2分之α=-tanα分之2

求证tan2分之α-1/tan2分之α=-tanα分之2求证tan2分之α-1/tan2分之α=-tanα分之2求证tan2分之α-1/tan2分之α=-tanα分之2(1)cosα=1/7,因为0<

cos4α×tan2α-sin4α=2tanα/(tan^2-1)过程!

cos4α×tan2α-sin4α=2tanα/(tan^2-1)过程!cos4α×tan2α-sin4α=2tanα/(tan^2-1)过程!cos4α×tan2α-sin4α=2tanα/(tan

2tanα/(1+tan²α)=sin2α?不是tan2α吗?

2tanα/(1+tan²α)=sin2α?不是tan2α吗?2tanα/(1+tan²α)=sin2α?不是tan2α吗?2tanα/(1+tan²α)=sin2α?不

已知tanα=1/2,求tan2α,tan(2α+π/3)的值

已知tanα=1/2,求tan2α,tan(2α+π/3)的值已知tanα=1/2,求tan2α,tan(2α+π/3)的值已知tanα=1/2,求tan2α,tan(2α+π/3)的值因tanα=1